The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1021/bi701424d
|View full text |Cite
|
Sign up to set email alerts
|

A New Ruthenium Complex To Study Single-Electron Reduction of the Pulsed OHState of Detergent-Solubilized Cytochrome Oxidase

Abstract: The first step in the catalytic cycle of cytochrome oxidase, the one-electron reduction of the fully oxidized enzyme, was investigated using a new photoactive binuclear ruthenium complex, [Ru(bipyrazine)2]2(quaterpyridine), (Ru2Z). The aim of the work was to examine differences in the redox kinetics resulting from pulsing the oxidase (i.e., fully reducing the enzyme followed by reoxidation) just prior to photoreduction. Recent reports indicate transient changes in the redox behavior of the metal centers upon p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…It is important to note that these calculated redox potentials differ substantially from the experimentally determined values (26) due to the fact that the latter are equilibrium potentials where charge compensation by protonation has occurred. The calculated O H /O H,R redox potentials are consistently ∼0.4 V higher than for the O/O R redox couples, which is in accord with the experimental observations of an elevated redox potential of Cu B in the O H state (29,52). The 0.4 V higher redox potential of the activated form solves the dilemma, at least in part, of an apparently far too low redox potential of the O→E transition to be consistent with proton pumping, and with the overall energetics of the catalytic cycle (2) (see The Metastable O H State).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is important to note that these calculated redox potentials differ substantially from the experimentally determined values (26) due to the fact that the latter are equilibrium potentials where charge compensation by protonation has occurred. The calculated O H /O H,R redox potentials are consistently ∼0.4 V higher than for the O/O R redox couples, which is in accord with the experimental observations of an elevated redox potential of Cu B in the O H state (29,52). The 0.4 V higher redox potential of the activated form solves the dilemma, at least in part, of an apparently far too low redox potential of the O→E transition to be consistent with proton pumping, and with the overall energetics of the catalytic cycle (2) (see The Metastable O H State).…”
Section: Discussionsupporting
confidence: 87%
“…However, in that study the observed rate of reduction of the BNC in the presumed O H state was much slower than reported in ref. 52 for the bovine and in ref. 29 for the Paracoccus enzyme.…”
Section: Discussionmentioning
confidence: 91%
“…When the partial reactions are examined the P → F and F → O rates are reportedly of the order of 10 000 s −1 [25,26], whereas the O → E and E → R rates are much lower (approx. 1000 s −1 ) [27,28]. The maximal levels of P and F will therefore be no more than 10 % those of E and O, and therefore undetectable with the present methodology.…”
Section: Resultsmentioning
confidence: 64%
“…The reaction proceeds via a fast electron transfer between Cu A and cytochrome a with an apparent lifetime of F of ~50 µs (rate constant of 2×10 4 s −1 ), 953,954 to form intermediate F′. Earlier work by Gray and coworkers estimated a shorter lifetime for intermediate F of 1.2–25 µs.…”
Section: Copper Active Sites That Activate Dioxygenmentioning
confidence: 99%
“…949,954 The formation of O H is pH dependent, slower at higher pH, with a k H / k D of 2.5 measured at pH 7.4 952 and is rate-limited by proton uptake. The transmembrane voltage generated is biphasic with rate constants of ~830 s −1 (coincident with electron transfer coupled to proton transfer) and 220 s −1 (associated with proton transfer) with relative amplitudes of 1:3.…”
Section: Copper Active Sites That Activate Dioxygenmentioning
confidence: 99%